Association of cardiovascular and fracture risks in women without clinical manifestations of atherosclerosis - I. A. Skripnikova; M. A. Kolchina; O. V. Kosmatova; M. A. Myagkova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study the associations of cardiovascular (CVR) and fracture risks using electronic versions of the SCORE (Systematic Coronary Risk Evaluation) and FRAX (Fracture Risk Assessment Tool) scores in women without clinical manifestations of atherosclerosis.Material and methods. This cross-sectional study included 200 female outpatients aged 45-69. All patients signed informed consent. The 10-year CVR was assessed using the high-risk SCORE charts. The 10-year risk of major osteoporotic fractures (MOF) and hip fractures was assessed using the Russian FRAX model. Bone mineral density (BMD) of the bones of the spine, femoral neck and proximal femur was measured using dual-energy X-ray absorptiometry. Statistical analysis was carried out using the Statistica.12.0, SPSS Statistics 26.0 and Excel 2016 software packages.Results. L ow CVR (SCORЕ <1%) was detected in 72 (36%) women, moderate (SCORЕ ≥1% and <5%) – in 124 (62%), and high (SCORЕ ≥ 5% and <10%) – in 4 (2%). Depending on the CVR degree, the patients were divided into 2 groups: group I – patients with SCORE <1 (low risk); group II – SCORE ≥1 (increased risk). Since bone mass is not the only but the main risk factor for fractures, the association between BMD and CVR was assessed. The SCORE ≥1 was identified in 128 women, of whom osteoporosis was diagnosed in 33 (26%), osteopenia – in 43 (34%) patients. The combination of increased CVR and absolute risk (AR) of major MOF was noted in 7 (5,5%) people. An inverse correlation was noted between CVR and BMD of the proximal femur and femoral neck. A positive correlation was also demonstrated between CVR (SCORE) and AR of MOFI and femoral neck fractures (FRAX). Multivariate regression (adjusted for age, body mass index, hypercholesterolemia) confirmed the reliability of a negative relationship between CVR and BMD of the lumbar vertebra.Conclusion. The data obtained confirm the hypothesis of multifaceted relationships of cardiovascular diseases caused by atherosclerosis with osteoporosis, manifested both at the clinical and preclinical levels, and at the level of risk formation, which makes it possible to recommend the cross-use of CVR and fracture AR scores for early primary prevention. This strategy will contribute to the early detection of combined pathology and timely preventive measures.